Special type of morphological reorganization induced by phorbol ester: reversible partition of cell into motile and stable domains. - Dugina, V B (1987)
The phorbol ester phorbol 12-myristate 13-acetate (PMA) induced reversible alteration of the shape of fibroblastic cells of certain transformed lines--namely, partition of the cells into two types of domains: motile body actively extending large lamellas and stable narrow cytoplasmic processes. Dynamic observations have shown that stable processes are formed from partially retracted lamellas and from contracted tail parts of cell bodies. Immunofluorescence microscopy and electron microscopy of platinum replicas of cytoskeleton have shown that PMA-induced narrow processes are rich in microtubules and intermediate filaments but relatively poor in actin microfilaments; in contrast, lamellas and cell bodies contained numerous microfilaments. Colcemid-induced depolymerization of microtubules led to contraction of PMA-induced processes; cytochalasin B prevented this contraction. It is suggested that PMA-induced separation of cell into motile and stable parts is due to directional movement of actin structures along the microtubular framework. Similar movements may play an important role in various normal morphogenetic processes.